The effect of knowledge management tools and knowledge process to the finished product weight difference in finished product inspection of a food manufacturing institution - Alpapara, Noridel Paul N.
This project was conducted to determine the effect of Knowledge Management (KM) initiatives to the finished product inspection process of a food manufacturing institution. An online KM assessment by the participants based in one of the commissaries of Apo Foods Corporation (AFC), and its external clients was done using a developed score sheet and questionnaire to establish the following : the top knowledge capability gap, and customer knowledge. This project also designed and implemented upgraded KM tools within the knowledge process based on the documented reports and studies. The effect of the project was measured based on the computed trend line using the finished product weight differences as dependent variable and time in days as independent variable.